2015
DOI: 10.1002/anie.201504504
|View full text |Cite
|
Sign up to set email alerts
|

Specific Photochemical Dehydrocoupling of N‐Heterocyclic Phosphanes and Their Use in the Photocatalytic Generation of Dihydrogen

Abstract: N-Heterocyclic phosphanes react under UV irradiation in a highly selective dehydrocoupling reaction to diphosphanes and H2. Computational studies suggest that the product formation is initiated by the formation of dimeric molecular associates whose electronic excitation yields H2 and a diphosphane. Combining the dehydrocoupling of sterically demanding phosphanes with Mg-reduction of the formed diphosphanes allows constructing a reaction cycle for the photocatalytic reductive generation of H2 from Et3NH(+).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…We found that 2 could be accessed in high yield and purity via reductive coupling of readily accessible 3‐Br with magnesium turnings in THF . An alternate synthesis of bis‐diazaphospholene 2 involves a photochemical dehydrocoupling, via the ultraviolet irradiation of hydride 3‐H with concomitant release of hydrogen, as reported by Nyulászi, Gudat and co‐workers (Equation 2, Scheme ) . These results indicate that illumination should be considered in investigations of the chemistry of 2 .…”
Section: Methodssupporting
confidence: 66%
“…We found that 2 could be accessed in high yield and purity via reductive coupling of readily accessible 3‐Br with magnesium turnings in THF . An alternate synthesis of bis‐diazaphospholene 2 involves a photochemical dehydrocoupling, via the ultraviolet irradiation of hydride 3‐H with concomitant release of hydrogen, as reported by Nyulászi, Gudat and co‐workers (Equation 2, Scheme ) . These results indicate that illumination should be considered in investigations of the chemistry of 2 .…”
Section: Methodssupporting
confidence: 66%
“…The targeted dimers 39 are readily extracted from reaction mixtures in a high yield. This transformation, together with Gudat's photochemical dehydrocoupling, 18 offers easy access to bisphosphines, avoiding complicated and harsh operations and workups required in other synthetic processes using metals such as sodium 38d and magnesium 38a-c . Furthermore, we attempted to design a new radical transformation by an integrated use of hydrogen atoms and electron transfers from N-heterocyclic phosphines.…”
Section: Applications In Synthesesmentioning
confidence: 99%
“…Combination of the reductive diphosphane splitting involved in this transformation with the photochemical dehydrocoupling of secondary NHPs (Scheme 12) led to the construction of another reaction cycle which enables the reductive generation of dihydrogen using a tertiary ammonium ion as the proton source and magnesium metal as the stoichiometric reductant (Scheme 14 (b)). 61 This process carries in essence the well-known reduction of H-acidic substrates by base metals to a basic and aprotic milieu by employing the H-DAP/bis-diazaphospholenyl couple as a smart photocatalyst that is needed to overcome the strong kinetic inhibition observed under these conditions and can be switched on and off by controlling the radiation source. CC-saturated NHPs can also be used as catalysts but are less active, the difference reflecting presumably the superior radical stabilizing efficiency of the DAP-based system.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…Thus, the bis-Scheme 14 (a) Reduction of Cl-DAPs to H-DAPs using Mg/Et 3 NHCl via disproportionation of diazaphospholonyl radicals as the key step (R = Dipp, 2-tBuC 6 H 4 ); 15 (b) photocatalytic reductive generation of H 2 (R = Dipp). 61 Both reactions can also be performed with CC-saturated NHPs. Generation of the bis-diazaphospholenyl in (b) can be performed in situ from a Br-NHP precursor.…”
Section: To New Frontiersring Opening Reactionsmentioning
confidence: 99%